GESTATIONAL WEIGHT GAIN AND RISK OF AUTISM SPECTRUM DISORDERS IN OFFSPRING : A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Autism, also known as Autism Spectrum Disorder (ASD), is a neurodevelopmental disorder characterized by abnormalities in social behavior, language skills, and communication abilities. A correlation was found between ASD patients and their mothers' excessive weight gain during pregnancy. However, the relationship between BMI before pregnancy and ASD incidence is inconclusive. In addition, research investigates the potential role that preventative factors, such as folate and fatty acid consumption, play in the development of the disease. There is growing evidence that certain factors, including advanced maternal and paternal age, valproate consumption, exposure to toxic chemicals, maternal diabetes, enhanced steroidogenic activity, immune activation, and possibly altered zinc–copper cycles and treatment with selective serotonin reuptake inhibitors, are associated with an increased risk of autism spectrum disorder in offspring. The large, multisite case-control study discovered that severe maternal obesity (obesity Class 2/3) was associated with approximately double the risk of ASD (with or without ID) and increased odds of DD. In the United States, an investigation was conducted. ASD was also associated with GWG when gestational age was considered, and this association was particularly strong in male offspring. Still, no connection between GWG and DD could be established. No correlations were found between the GWG rate and ASD or DD when the data was evaluated based on how well it matched clinical recommendations. Patients with autism spectrum disorder whose mothers gained an unhealthy quantity of weight during pregnancy were found to have a correlation. However, there is little correlation between BMI before pregnancy and the risk of having a child with autism spectrum disorder (ASD).